Development of System Solution for Public Transport System Sustainability and Adapting it to the Challenge of COVID-19 - Patlins, Antons (Transportation Research Procedia, 2021)
The main goal of current article is to offer a system solution for keeping public transport system in sustainable and safe position by adapting it to the COVID-19 challenge, ensuring its sustainability. The introduction of the paper deals with the analysis of the public transport system in 2020 under the unclear epidemiological situation in the World by spread of Covid-19. Second chapter shows the beginning of the process of planning of system solution for adapting the public transport system to the challenge of Covid-19. Author deals with own vision of such solution. In third chapter author shows the vision of the system solution for the control of public transport system to ensure its sustainability taking into account also epidemiological situation. Last chapter shows some ideas, advanced practices and last achievements for public transport system sustainability.